SERS-based lateral flow immunoassay for rapid and sensitive sensing of nucleocapsid protein toward SARS-CoV-2 screening in clinical samples - Zhi, Weixia; Wang, Lingwei; Dai, Li; Xu, Jing; He, Tingting; Zong, Xiangxin; Xu, Jun; Cai, Huaihong; Pi, Jiang; Sun, Pinghua; Chen, Shanze; Huang, Xueqin; et al. (Analytica chimica acta, 2025)
Early and accurate identification of SARS-CoV-2 infection is crucial for epidemic prevention and control. Lateral flow immunoassay (LFIA) has become the mainstream method for screening SARS-CoV-2 infection due to its rapid, simple and amenable for point-of-care detection (POCT), but still suffered from the poor sensitivity and accuracy. In this study, Au nanoparticles (NPs) with controllable Ag shell (Au@Ag) were manufactured via a seed-mediated growth method. The Au@Ag-based LFIA exhibited superb colorimetric (CM) signal and intense surface-enhanced Raman scattering (SERS) signal for dual-mode sensing of nucleocapsid protein (N protein), a naturally protein expression in vivo during SARS-CoV-2 infection. The limit of detection (LOD) of the SERS-LFIA mode was 2.16 pg/mL, which was around 150-time more sensitive than conventional visual CM-LFIA mode (300 pg/mL). More importantly, the proposed LFIA is capable of quantitatively detecting N protein-spiked real samples with satisfactory recoveries from 83 % to 91.4 %. Clinical pharyngeal swab samples of the infected patients (n = 20) and healthy subjects (n = 20) were effectively discriminated in the developed SERS-LFIA, where the negative accuracy rate was 100 % and the positive accuracy rate was 85 %, among which samples from P1, P18, and P19 were false-negative results. The results obtained from the LFIA immunoassay were in good agreement with the standard PCR method in clinic, and superior to those of the commercially colloidal gold strip by using the same antibodies. In conclusion, the LFIA proposed here can perform specific, rapid, and ultrasensitive analysis of N protein toward early warning of SARS-CoV-2 infection. Our study proposed a multilayer Au@Ag NP with tunable plasmonic core-shell structure as a versatile probe, and conjugated them with lateral flow immunoassay (LFIA) for colormetric (CM-LFIA) and SERS (SERS-LFIA) multi-model sensing antigen-nucleocapsid protein (N protein) toward SARS-CoV-2 screening in complex biological matrix. Practical analysis of clinical samples demonstrated the availability of our developed LFIA, that is capable of identifying the infected subjects (N = 20) from healthy candidates (N = 20). The results were in good agreement with the clinical PCR method, and dramatically superior to the commercially available LFIA strips. [Display omitted] •The study detected the N protein originated from SARS-CoV-2.•This LFIA immunoassay was completed in only 12 min.•Colorimetric/SERS-LFIA can overcome the insufficient adaptability of single signal.•his LFIA can distinguish the infected patients from healthy subjects.